School Vouchers and Public School Productivity - The Case of the Swedish Large Scale Voucher Program - Staffan Waldo (Lund University, School of Economics and Management, Department of Economics, 2006)
Since the school voucher reform in 1992/93 Sweden has experienced a rapid increase in private schools. School regulations allow private and public schools to compete for students on very similar terms. This makes the Swedish educational market interesting for studying how competition affects the provision of education. In this study competition and public school productivity are analyzed for 105 urban municipalities during the period 1998/99 to 2001/02. The empirical estimations are performed in two stages. In the first stage, productivity is estimated using Data Envelopment Analysis (DEA) and a Malmquist productivity index. In the second stage, the estimated productivity is regressed on private school competition and a number of control variables. We cannot reject competition to be exogenous in a Hausman test. The coefficient for competition is not significant at the 5 percent level in any of the empirical specifications.
Keywords: H73; I21; 330; Malmquist index; competition; education